2009
DOI: 10.1177/0146167208329512
|View full text |Cite
|
Sign up to set email alerts
|

Approach—Avoidance Motivation and Information Processing: A Cross-Cultural Analysis

Abstract: Much recent research suggests that North Americans more frequently experience approach motivations and East Asians more frequently experience avoidance motivations. The current research explores some cognitive implications of this cultural difference. North Americans should be more attentive to approach-oriented information, whereas East Asians should be more attentive to avoidance-oriented information. Three studies confirmed this hypothesis. When asked to recall information framed in either approach or avoid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(125 citation statements)
references
References 28 publications
2
121
0
2
Order By: Relevance
“…Higgins (1998) defined self-regulatory focus as the way in which individuals choose goals and motivate themselves to achieve those goals. Two distinct regulatory systems are generally discussed in self-regulatory focus theory: approach motivation and avoidance motivation (Gray, 1990), Individuals with approach motivation exhibit high vigilance for positive stimuli and strong behavioral tendencies to pursue positive stimuli (Hamamura, Meijer, Heine, Kamaya, & Hod, 2009). In contrast, avoidance motivation is a general sensitivity to negative stimuli in the environment and a strong behavioral tendency to avoid aversive stimuli (Elliot & Harackiewicz, 1996).…”
Section: Approach-avoidance Motivation Hieorymentioning
confidence: 99%
“…Higgins (1998) defined self-regulatory focus as the way in which individuals choose goals and motivate themselves to achieve those goals. Two distinct regulatory systems are generally discussed in self-regulatory focus theory: approach motivation and avoidance motivation (Gray, 1990), Individuals with approach motivation exhibit high vigilance for positive stimuli and strong behavioral tendencies to pursue positive stimuli (Hamamura, Meijer, Heine, Kamaya, & Hod, 2009). In contrast, avoidance motivation is a general sensitivity to negative stimuli in the environment and a strong behavioral tendency to avoid aversive stimuli (Elliot & Harackiewicz, 1996).…”
Section: Approach-avoidance Motivation Hieorymentioning
confidence: 99%
“…First, it is possible that our results vary as a function of cultural context. In particular, Western cultures are more likely to encourage approach motivation, whereas non Western cultures are more likely to encourage avoidance motivation (e.g., Hamamura, Meijer, Heine, Kamaya, & Hori, 2009). Consequently, the relations between approach, avoidance, problem-solving, and social integration may be different in non Western cultures.…”
Section: Limitations and Future Researchmentioning
confidence: 99%
“…In a group that did not receive message framing, which did not match their culture, the findings were similar to people who did not receive any messages 44 . on the contrary, Hamamura et al, found that Japanese students remembered more loss-frame information, while American students remembered more gain-frame information 45 .…”
Section: Discussionmentioning
confidence: 92%